2023
DOI: 10.3390/v15091939
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Indirect ELISA for the Detection of African Swine Fever Virus Antibodies Using a Tag-Free p15 Protein Antigen

Zhi Wu,
Huipeng Lu,
Dewei Zhu
et al.

Abstract: African swine fever (ASF) is one of the most severe diseases caused by the ASF virus (ASFV), causing massive economic losses to the global pig industry. Serological tests are important in ASF epidemiological surveillance, and more antigen targets are needed to meet market demand for ASFV antibody detection. In the present study, ASFV p15 protein was fusion-expressed in Escherichia coli (E. coli) with elastin-like polypeptide (ELP), and the ELP-p15 protein was purified using a simple inverse transition cycling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Moreover, the sensitivity test of the developed ELISA was evaluated in the present assessment and the result showed that the current ELISA kit was capable of detecting a commercially positive ASFV serum at a high dilution of 1:32, which is consistent with the results of a previous study [17]. In addition, the agreement rate between the k3-iELISA and INGENASA's commercial ASFV antibody detection kit was 99.00% [14,16]. These results emphasize the significant clinical potential of the k3-iELISA.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Moreover, the sensitivity test of the developed ELISA was evaluated in the present assessment and the result showed that the current ELISA kit was capable of detecting a commercially positive ASFV serum at a high dilution of 1:32, which is consistent with the results of a previous study [17]. In addition, the agreement rate between the k3-iELISA and INGENASA's commercial ASFV antibody detection kit was 99.00% [14,16]. These results emphasize the significant clinical potential of the k3-iELISA.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, the samples were tested using a commercial ASFV antibody detection kit (Ingenasa, Madrid, Spain) provided by Qingdao RealVet Bio-Technology Co., Ltd., Qingdao, China. (ASF.K001/5) based on the p72 protein for comparison with the established ELISA method as previously described [1,16]. This comparison aimed to determine the effectiveness and coincidence rate, evaluating the consistency between the established ELISA and the commercial kit based on the test results of each sample.…”
Section: Detection Of Clinical Samples and Comparison With The Commer...mentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies include p30 and p54 proteins as potential indicators [ 87 ]. The last studies using new antigens include core–shell protein p15 [ 88 ], transmembrane protein pI329L [ 83 ] or K205R protein [ 89 ]…”
Section: Discussionmentioning
confidence: 99%